Editorial: What could second-generation research on the doctorate be like? - Jonathan D. Jansen (Perspectives in Education, 2011)
From text: This seminal collection of conceptual and empirical articles on the doctorate propels higher education scholarship in South Africa into new territory. We have simply not spent much time thinking about higher degrees and especially not about the doctorate. There is a wealth of scholarship on the governance and organisation of higher education, the founding legislation and policies that govern post-school education after apartheid, the problems of equity, access and success in higher learning given the poverty of the school system, and the persistent legacies of racism and authoritarianism inside universities. The formal arrangements for rearranging universities (mergers and incorporations, for example), inscribing new curriculum codes (the SAQA-inspired regulations), assuring quality (the industry spawned by the Council on Higher Education), and transforming patterns of racial enrolments and appointments have all enjoyed considerable “air time” in journals and some books.